1992
DOI: 10.1159/000236124
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aeroallergen-lnduced Bronchial Eosinophilia by Azelastine in Guinea Pigs

Abstract: The ability of azelastine to influence allergic bronchial eosinophil infiltration in guinea pigs was studied. Aeroallergen challenge of actively sensitized guinea pigs produces eosinophil infiltration in bronchoalveolar lavage fluid collected 20–24 h after aeroallergen exposure. Azelastine and methylprednisolone, administered orally 2 h before challenge, inhibited eosinophilic infiltration yielding the ED50s of 1.55 and 4.48 mg/kg, respectively. WEB-2086, a platelet-activating factor antagonist (3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In the present study, histologie findings showed a lower number of inflammatory cells and mast cells in the mucosa at the pharyngeal orifice of the eustachian tube in animals without MEE than in those with MEE, in all groups except group D. Previous studies have demonstrated that AZ effectively inhibits allergic eosinophil infiltration and neutrophil infiltration in animals. 3031 Therefore, the results of the present study support the theory that AZ suppresses the allergic reaction in the nasopharynx around the eustachian tube. Thus, AZ administration appeared to lead to improvement in eustachian tube function and result in clearance of MEE.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, histologie findings showed a lower number of inflammatory cells and mast cells in the mucosa at the pharyngeal orifice of the eustachian tube in animals without MEE than in those with MEE, in all groups except group D. Previous studies have demonstrated that AZ effectively inhibits allergic eosinophil infiltration and neutrophil infiltration in animals. 3031 Therefore, the results of the present study support the theory that AZ suppresses the allergic reaction in the nasopharynx around the eustachian tube. Thus, AZ administration appeared to lead to improvement in eustachian tube function and result in clearance of MEE.…”
Section: Discussionsupporting
confidence: 87%
“…Azelastine re duces BAL eosinophils in guinea pigs [12] and inhibits eosi nophil migration into the bronchi of dogs following antigen challenge [21], In addition, azelastine prevents eosinophil degranulation [22] and activation [23]. The release of gran ule proteins from eosinophils damages the airway epitheli um and augments airway hyperresponsiveness [24], The findings o f those EG2-positivc eosinophils decreased after azelastine treatment are supporting its anti-inflammatory action.…”
Section: Discussionmentioning
confidence: 98%
“…Azelastic is a novel compound with a broad spectrum of pharmac ological activity on airway inflammatory and smooth mus cle response [6], Azelastine acts as an inhibitor o f the syn thesis and release of bronchospastic mediators (e.g., histamine and serotonin) from mast cells, eosinophils, and other cells, following immunological ornonimmunological stimulation [7][8][9][10][11]. Azelastine inhibits allergic eosinophil infiltration in bronchoalveolar lavage (BAL) [12] and neu trophils in the lungs of guinea pigs [13]. Therapy with aze lastine has helped patients with asthma to reduce their use of concomitant antiasthma medications and has also decreased or stabilized asthma symptoms [14].…”
Section: Introductionmentioning
confidence: 99%